The Effect Of Giving Red Ginger Brew To Reduce Blood Sugar Levels In Type Ii Diabetes Mellitus Patients At Hospital X (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2024)
Background: Diabetes mellitus is a chronic disease that attacks the body's metabolic system which is characterized by an increase in blood glucose levels due to insulin secretion, insulin action or both. Objective: The aim of this nursing care is to understand, explain and apply evidence-based practices in professional nursing. Red ginger decoction is used to reduce blood sugar levels in Type II Diabetes Mellitus patients at the Hospital X. Research Method: The evident based ckinical practice design used was the Quasy Experiment, especially the pretest-posttest design. Namely by conducting observations before and after the control group intervention. There were two intervention groups, namely 2 groups who were given ginger decoction to reduce blood sugar levels in Type II Diabetes Mellitus patients for 4 consecutive days and done 2 times a day.Results: The mean blood glucose in DM patients (175gr/dl) with a p-value (0.034) or less than the significance value of p-value <0.05 (0.034), which means there is a difference in blood glucose levels in the intervention group and the control group. Conclusion: There is a significant effect of giving red ginger decoction on reducing blood glucose levels in type 2 DM patients after intervention Keywords: Diabetes Mellitus, Blood Sugar Levels, Red Ginger Decoction